Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 7 - Rational Functions - 7.3 Multiplying and Dividing Rational Expressions - 7.3 Exercises: 11

Answer

$= -\frac{1}{2} $

Work Step by Step

$\frac{2(x-4)}{4x+20} \times \frac{3(x+5)}{12-3x}$ $= \frac{2(x-4)}{4(x+5)} \times \frac{3(x+5)}{3(4-x)}$ $= \frac{6(x-4)(x+5)}{12(x+5)(4-x)} $ $= \frac{6(x-4)(x+5)}{12(x+5)(-(x-4))} $ $= \frac{6(x+5)}{-12(x+5)} $ $= -\frac{6(x+5)}{12(x+5)} $ $= -\frac{6}{12} $ $= -\frac{1}{2} $
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.